The Role of Gap Junctions in the Generation of Smooth Muscle Cells from Bone Marrow Mesenchymal Stem Cells. (12th August 2022) - Wang, Ying; Yang, Boping; Hu, Pan; Lu, Shentao; Lei, Li; Liu, Lubin
Abstract : Background . Studies have shown that stem cell transplantation can improve smooth muscle cell (SMC) regeneration and remodelling. Gap junctions can enhance the cytoprotective effects of neighbouring cells. We investigated the effect of gap junctions on the differentiation of bone marrow mesenchymal stem cells (BMSCs) into SMCs. Materials and Methods . Rat BMSCs and SMCs were obtained from the bone marrow and bladder of Sprague-Dawley rats, respectively. Flow cytometry and multilineage differentiation were performed to assess the characteristics of these cells. BMSCs and SMCs were incubated together in cocultures in the presence and absence of heptanol, an uncoupler of gap junctions. Cocultures were divided into three groups consisting of a contact coculture, noncontact coculture, and contact coculture plus heptanol groups. The expression of BMSC-specific markers and the effect of gap junctions on the differentiation of BMSCs were evaluated by performing real-time reverse transcription-polymerase chain reaction, immunofluorescence analysis, and western blotting after cocultures. Results . CD90 and CD44 were markedly expressed, and CD31 and CD45 were weakly or not expressed in BMSCs. The cells also showed good osteogenic and adipogenic differentiation ability. Compared with the noncontact coculture group, the SMC markers such as α -SMA, calponin, and connexin43 increased in the contact coculture group. The effect of contact in the coculture group was significantly weakened by heptanol. Conclusions . The results suggested that gap junctions play an important role in the generation of SMCs from BMSCs. The formation of SMCs can potentially be used to repair the sphincter muscle of patients with stress urinary incontinence.